Hip precautions after hip operation (HippityHop): protocol for a before and after study evaluating hip precautions following total hip replacement - Lightfoot, C.J.; Sehat, K.R.; Drury, G.; Brewin, C.; Coole, C.; Drummond, Avril E.R. (SAGE, 2018)
Introduction Hip precautions are routinely used despite inconclusive evidence that they reduce dislocations, and concern that they impede activities of daily living. HippityHop compares a change in practice locally from implementing routine hip precautions to no routine precautions, in order to: 1. Compare patient outcomes in quality of life, functional performance, pain, sleep, mood and satisfaction. 2. Ascertain staff and patient perceptions of the two regimes. 3. Determine the cost of precautions.